Ultraviolet-Induced Cross-Links in the Deoxyribonucleic Acid of Single-Stranded Deoxyribonucleic Acid Viruses as a Probe of Deoxyribonucleic Acid Packaging - Francke, Bertold (1972)
Deoxyribonucleic acid (DNA) from ultraviolet (UV)-irradiated φX174 sediments in alkali at rates up to 1.7 times that of unirradiated φX174 DNA and is observed as a condensed, cross-linked structure when examined in the electron microscope by the formamide spreading technique. This structure appears to result from multiple cross-links induced in the tightly coiled DNA contained within the spherical φX174 capsid. In contrast, the DNA extracted after UV irradiation of the filamentous bacteriophage M13 is not strikingly altered in its sedimentation properties and appears by electron microscopy to be rod-shaped as a result of side-to-side association of the circular DNA. The differences in these UV-induced structures reflect the differences in the packaging of the single-stranded DNA in the two virions.